Fertilization effect on the growth of Retrophyllum rospigliosii of the Andean zone of Colombia - Ramírez, Jorge Andrés; Marín, Adriana; Urrego, John Byron; Castaño, Álvaro; Ospina, Román (Instituto de Ecología, A.C., 2021)
Retrophyllum rospigliosii (Podocarpaceae) is a native conifer species of high Andean forests that is currently under endangered status. To evaluate if the fertilization of the soil improves the yield of R. rospigliosii stands, a plantation of this species was established in the Colombian Andean zone in 1999 and monitored over time (years: 2003, 2004, 2006, 2008, 2009, 2010, 2016 and 2018). A longitudinal analysis was performed using a linear mixed model to evaluate the effect of fertilization treatments on growth of R. rospigliosii. Average growth rates found in this plantation were slightly higher than those reported for this species, but slower compared to other coniferous species commonly planted in the Colombian Andean zone. The average annual increment in diameter, height, basal area, and volume in the control treatment was 12 mm, 0.661 m, 2.050 m2 ha-1 and 0.012 m3, respectively. The fertilization treatment number 6 (50 kg ha-1 of N, 20 kg ha-1 of P, 2 kg ha-1 of B y 5.5 kg ha-1 of trace elements) showed a significant increase in the growth variables evaluated relative to the control (9.2%, 8.4%, 18.4% and 25.0%, respectively for diameter, height, basal area, and volume) during the study period. This is possibly because early fertilization favors early crown closure and weed reduction, which, added to the adaptations of this species to low soil nutrient availability, maintains the effect over time.